Considerations for management strategy evaluation for small pelagic fishes. Issue 6 (12th June 2021) - Siple, Margaret C.; Koehn, Laura E.; Johnson, Kelli F.; Punt, André E.; Canales, T. Mariella; Carpi, Piera; de Moor, Carryn L.; De Oliveira, José A. A.; Gao, Jin; Jacobsen, Nis S.; Lam, Mimi E.; Licandeo, Roberto; et al.
Abstract: Management strategy evaluation (MSE) is the state‐of‐the‐art approach for testing and comparing management strategies in a way that accounts for multiple sources of uncertainty (e.g. monitoring, estimation, and implementation). Management strategy evaluation can help identify management strategies that are robust to uncertainty about the life history of the target species and its relationship to other species in the food web. Small pelagic fish (e.g. anchovy, herring and sardine) fulfil an important ecological role in marine food webs and present challenges to the use of MSE and other simulation‐based evaluation approaches. This is due to considerable stochastic variation in their ecology and life history, which leads to substantial observation and process uncertainty. Here, we summarize the current state of MSE for small pelagic fishes worldwide. We leverage expert input from ecologists and modellers to draw attention to sources of process and observation uncertainty for small pelagic species, providing examples from geographical regions where these species are ecologically, economically and culturally important. Temporal variation in recruitment and other life‐history rates, spatial structure and movement, and species interactions are key considerations for small pelagic fishes. We discuss tools for building these into the MSE process, with examples from existing fisheries. We argue that model complexity should be informed by management priorities and whether ecosystem information will be used to generate dynamics or to inform reference points. We recommend that our list of considerations be used in the initial phases of the MSE process for small pelagic fishes or to build complexity on existing single‐species models.